Homo multiplex. Science Fiction, Statute of the Imagination and the Post-Human. - Poccia, Daniele; Gigliozzi, Gianluca (Scenari, 2021)
The article investigates a set of science-fiction works that in the last twenty years have revealed a new ontological situation and a new anthropological condition. According to a knew diagnosis, since the 1980s there has been a break with the expectations of socio-political change nurtured in Modernity. However, a deep split has opened subsequently between knowledge and power, which has rearranged the relationship between concepts and objects, words and things. Faced with the resulting practical impotence, the article investigates the possibility to use science fiction narratives – considered as a form of critical mythopoeia – in view of the comprehension of our situation and of the transformation of the existing.